2012
DOI: 10.1121/1.3672700
|View full text |Cite
|
Sign up to set email alerts
|

Contactless transport of matter in the first five resonance modes of a line-focused acoustic manipulator

Abstract: The first five resonance modes for transport of matter in a line-focused acoustic levitation system are investigated. Contactless transport was achieved by varying the height between the radiating plate and the reflector. Transport and levitation of droplets in particular involve two limits of the acoustic forces. The lower limit corresponds to the minimum force required to overcome the gravitational force. The upper limit corresponds to the maximum acoustic pressure beyond which atomization of the droplet occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Owing to its material independency, acoustic levitation has found a wide spectrum of applications in contactless processing and analysis of liquid samples (Trinh, Thiessen & Holt 1998;Yarin, Pfaffenlehner & Tropea 1998). The contactless manipulation and transportation of particles and droplets is one of the most interesting challenges in the acoustic levitation field (Koyama & Nakamura 2010;Foresti et al 2011;Foresti, Nabavi & Poulikakos 2012) with applications ranging from the handling of living cells in lab-on-a-chip devices (Bruus et al 2011) to millimetre-size sample manipulations in air (Bjelobrk et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Owing to its material independency, acoustic levitation has found a wide spectrum of applications in contactless processing and analysis of liquid samples (Trinh, Thiessen & Holt 1998;Yarin, Pfaffenlehner & Tropea 1998). The contactless manipulation and transportation of particles and droplets is one of the most interesting challenges in the acoustic levitation field (Koyama & Nakamura 2010;Foresti et al 2011;Foresti, Nabavi & Poulikakos 2012) with applications ranging from the handling of living cells in lab-on-a-chip devices (Bruus et al 2011) to millimetre-size sample manipulations in air (Bjelobrk et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…After the results presented above, we can explain quantitatively the significant improvement that the herein presented technique brings to the contactless droplet transportation compared to the state of the art. The numerical results reported by Foresti et al 34 showed that for the line-focussed levitator used in this study, the maximum volume of the water droplet that could be safely levitated, and transported by H regulation through the two acoustic resonances in the H 1 mode is 0.9 nl. With the presented control technique, by adjusting V d based on the aspect ratio of the droplet, we are able to levitate and transport water droplets of 1.9 ll in volume, which means a volume increase by three orders of magnitude.…”
Section: Resultsmentioning
confidence: 53%
“…3C). We note that a linear improvement is expected with increasing driving frequency, because the absolute dimensions of the system scale with the acoustic wavelength ( 31 ). In addition, for the same acoustic pressure amplitude and droplet diameter, the acoustophoretic force increases linearly with the frequency.…”
Section: Resultsmentioning
confidence: 94%